2014
DOI: 10.1073/pnas.1323977111
|View full text |Cite
|
Sign up to set email alerts
|

Farnesoid X receptor (FXR) gene deficiency impairs urine concentration in mice

Abstract: The farnesoid X receptor (FXR) is a ligand-activated transcription factor belonging to the nuclear receptor superfamily. FXR is mainly expressed in liver and small intestine, where it plays an important role in bile acid, lipid, and glucose metabolism. The kidney also has a high FXR expression level, with its physiological function unknown. Here we demonstrate that FXR is ubiquitously distributed in renal tubules. FXR agonist treatment significantly lowered urine volume and increased urine osmolality, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 41 publications
4
73
0
Order By: Relevance
“…To verify whether EP4 was regulated in renal CDs during the process of urinary concentration, mouse primary inner medullary collecting duct (IMCD) cells were cultured as described previously (18). Hyperosmotic challenge (700-900 mOsm/kg H 2 O) induced EP4 protein expression in IMCD cells (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To verify whether EP4 was regulated in renal CDs during the process of urinary concentration, mouse primary inner medullary collecting duct (IMCD) cells were cultured as described previously (18). Hyperosmotic challenge (700-900 mOsm/kg H 2 O) induced EP4 protein expression in IMCD cells (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, fFN is absent from cervicovaginal secretions from 24 weeks until near term; however, 3-4% of women undergoing routine screening at 24-26 weeks are positive, and are at substantially increased risk of preterm delivery [9]. However, it has been less informative for the determination of term or PTB due to the limited two week window of accuracy of the clinical test [10]. Therefore, a novel biomarker is needed which can provide more accurate time of delivery or any correlation between the levels of a particular analyte and prediction of PTB.…”
Section: Introductionmentioning
confidence: 99%
“…FXR orchestrates urine volume in mice. FXR activation reduces urine volume and increases urine osmolality in animals through induction of apical aquaporin 2 (AQP2; Zhang et al 2014). In contrast, with a reduction in osmolality, there was an increased urine output in FXRnull mice, suggesting the ability of FXR to concentrate urine became attenuated in FXR-null mice.…”
Section: Fxr and Kidney Homeostasismentioning
confidence: 99%
“…A heterodimer is formed with retinoid X receptor (RXR) by FXR when binding is initiated by endogenous ligands, the binding with BAs initiates the RXR/FXR heterodimer binding to the FXR response element which is located in the promoter regions of FXR target genes. An abundant expression of FXR has been reported in the hepatic liver as well as adrenal glands, kidney, and intestinal tract (Forman et al 1995;Lee et al 2006;Modica et al 2008Modica et al , 2010Zhang et al 2014), where it functions as an intracellular sensor of BAs to control BA synthesis in the liver (Makishima et al 1999;Lu et al 2000;Chiang 2002;Li-Hawkins et al 2002;Wang et al 2002). Recent discoveries have demonstrated that FXR is responsible to regulate hepatic glucose production, lipid metabolism, liver regeneration, intestinal homeostasis, function of pancreatic β cells, and urine concentration in the kidney (Edwards et al 2002;Huang et al 2006;Jiang et al 2007;Popescu et al 2010;Renga et al 2010;Zhang et al 2004Zhang et al , 2006Zhang et al , 2014.…”
Section: Introductionmentioning
confidence: 99%